2013
DOI: 10.1007/s12262-013-0931-3
|View full text |Cite
|
Sign up to set email alerts
|

The Intramedullary Nailing of Adult Femoral Shaft Fracture by the Way of Open Reduction is a Disadvantage or Not?

Abstract: The purpose of this study is that to evaluate superiority and results of open technique in the treatment of femoral shaft fracture with interlocking intramedullary nailing. The retrospective study is designed to evaluate results of our technique. In this study, the patients that were admitted to the Orthopedics and Traumatology Department of University Hospital that is third level of trauma center. We claim that open technique is not a disadvantage during union process over closed technique in treatment of fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Further supporting the notion of trochanteric entry nails, another study on cadavers found lesser structural and iatrogenic injury to the surrounding structures and the gluteal musculature with trochanteric nailings [35]. In our series, open reduction was performed in about one-third of patients and this approach is secondary to di cult closed reduction procedure that has consistently been described as a safe alternative technique [36,37]. In this study, external xation for the treatment of femoral shaft was primarily done for open fractures.…”
Section: Discussionsupporting
confidence: 72%
“…Further supporting the notion of trochanteric entry nails, another study on cadavers found lesser structural and iatrogenic injury to the surrounding structures and the gluteal musculature with trochanteric nailings [35]. In our series, open reduction was performed in about one-third of patients and this approach is secondary to di cult closed reduction procedure that has consistently been described as a safe alternative technique [36,37]. In this study, external xation for the treatment of femoral shaft was primarily done for open fractures.…”
Section: Discussionsupporting
confidence: 72%
“…Damage to the surrounding soft tissues, such as the periostea, muscles, and vessels, was suspected to be worse in these fracture patterns, and additional damage due to open reduction itself could have adversely affected bony union. Burç et al 23 reported that for 44 patients with femoral shaft fractures with open reduction, the complete union rate was 90.9% for 40 patients; the non-union rate was 9.1% for four patients who underwent IMN. They concluded that the open technique was acceptable because the results of their study were similar to the results of the closed IMN technique in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure would seriously damage the blood supply of fragments, which may lead to atrophic nonunion of the fracture (Fig. 4 ) 15 , 16 . Thus, a relatively high incidence of atrophic nonunion was observed in this study.…”
Section: Discussionmentioning
confidence: 99%